Clemency, Asset Restitution, and Islamic Law: Rethinking Justice for Corruption Offences in Indonesia - Liantha Adam Nasution; Fatimah Islamy Nasution; Siti Aminah; Zulfahmi Zulfahmi (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
The practice of granting clemency to corruption offenders who return misappropriated assets remains insufficiently examined within the framework of Islamic law, giving rise to an unresolved tension between humanitarian considerations and substantive justice. While existing studies have largely addressed clemency and asset recovery from the perspective of positive law, scholarly attention to their normative implications in Islamic law remains limited, particularly with regard to ghulul (the misappropriation of public wealth), the obligation of restitution (rad al-mazalim), and preventive sanctions (tazir). This article critically examines whether granting clemency to corrupt offenders who return assets can be justified under Islamic law, while also assessing its compatibility with Indonesia’s positive legal system. This study employs a juridical-normative approach by analysing primary legal materials, including presidential regulations on clemency and statutory provisions on corruption eradication, alongside classical and contemporary Islamic legal sources. The findings indicate that although clemency in positive law may function as a humanitarian and rehabilitative instrument, its legitimacy must be contingent upon full asset restitution and a careful evaluation of its socio-economic impact. From an Islamic legal perspective, sincere repentance (taubat nasuha) accompanied by restitution constitutes an absolute moral and legal obligation; however, it does not negate the necessity of tazir sanctions as a deterrent mechanism to safeguard the public interest and prevent the recurrence of similar offences. This article underscores the need to reconceptualise justice in the adjudication of corruption cases through the integration of Islamic legal principles into clemency and asset restitution policies, with the aim of establishing a more comprehensive and substantively just framework for corruption eradication in Indonesia.